First Principles Study of Layered CrGeTe3 as Lithium Intercalation Compound. Issue 4 (1st April 2022) - Ahmed, Sheraz; Alkhedher, Mohammad; Isa, Muhammad; Majid, Abdul
Abstract : There have been unprecedented research efforts to produce efficient and sustainable electrode materials for lithium-ion batteries (LIB). The research efforts to increase energy density, life cycle, safety, and rate-capability are still in progress. This work is carried out to explore the prospects of a new anode material CrGeTe3 for use in LIB studied via first-principles predictions. The investigation of Li: CrGeTe3 system and lithiation mechanism in the proposed material pointed out its suitability for lithium intercalation compound. The energy-profiling at highly symmetry points in the host structure revealed that BGe-Cr is most favorable energy site for lithiation in the material. The maximum value of the lithium insertion voltage is 3.41 V and the storage capacity is 620.60 mAh g −1 . The diffusion barrier faced by lithium atom is 0.27 eV which is the minimum value, while moving along the x -axis within the top and middle hexagonal rings. The steric interaction of Li with Ge and Te atoms pointed structural reliability and hence stable operation of the anode to address capacity fading problems in LIB.